Differential Elliptic Flow Analysis of Hadrons with Different Wuark Content in Simulated pp Collisions - Osama, Elhussein (AUC Knowledge Fountain, 2024)
According to current physics theories, it is assumed that in the first microsecond after the big bang, the universe was in a state of matter called Quark-Gluon Plasma (QGP), where the fundamental consistent of matters (quarks and leptons), were highly energetic, and floating around freely. Searching for such phase of matter; as the possible earliest signatures after the big bang, and among many other interesting experimental measurements, the jet quenching and elliptic flow are the most important ones, in the heavy ion collisions at the Relativistic Heavy Ion Collider (RHIC) and the Large Hadron Collider (LHC) experiments. The azimuthal anisotropy of the produced particles with respect to the reaction plane angle is commonly quantified via the elliptic flow parameter, . The absence of elliptic flow for the electromagnetically and weakly interacting particles (, in addition to the universal features of the number of quarks scaling for the elliptic flow parameter of the strongly interacting particles (hadrons), have concluded that the development of partonic collectivity during the QGP phase and before hadronization. Furthermore, the hydrodynamic models; assuming thermalization, have perfectly described the data at low transverse momentum incorporating an equation of state for the QGP. Nevertheless, the unexpected measured non-zero finite values of for hadrons at high transverse momentum, as well as the similar suppressions for the away side yields - where the away side is the opposite direction from where the collision occurred, and yield means the number of particles produced from the collision - of direct photons and neutral pions, present a challenge. Existing models, such as jet-quenching models have encountered difficulties in accurately describing such data. Furthermore, the surprising similarity in the measured values between heavy flavor and light quarks raises questions about the thermalization of heavy quarks within the produced medium, a phenomenon that remains inadequately understood. These intriguing puzzles have prompted a critical examination of potential non-flow contributions to the measurements, as their presence could significantly impact the imposed constraints on medium transport parameters, e.g., viscosity and entropy. After all, the reaction plane angle is not directly measurable quantity in the experiment, and it depends on commonly used techniques; and there might be biases due to the method itself. The major non-flow contributions might arise from the jet fragmentation and its underlying mechanisms. PYTHIA simulation is an ideal environment to unfold the contributions from the jet fragmentation, as it contains no final state interactions. Accordingly, the aim of the presented work is to further validate the experimental results, using the same techniques as in the experimental work in determining the reaction plane angle and measuring the elliptic flow parameter , using PYTHIA. PYTHIA was used to generate the data and simulating the high energy collisions at center-of-mass energies of GeV at RHIC and TeV at the LHC. According to current physics theories, it is assumed that in the first microsecond after the big bang, the universe was in a state of matter called Quark-Gluon Plasma (QGP), where the fundamental consistent of matters (quarks and leptons), were highly energetic, and floating around freely. Searching for such phase of matter; as the possible earliest signatures after the big bang, and among many other interesting experimental measurements, the jet quenching and elliptic flow are the most important ones, in the heavy ion collisions at the Relativistic Heavy Ion Collider (RHIC) and the Large Hadron Collider (LHC) experiments.The azimuthal anisotropy of the produced particles with respect to the reaction plane angle is commonly quantified via the elliptic flow parameter, 𝑣2. The absence of elliptic flow for the electromagnetically and weakly interacting particles (𝛾,𝑊±,𝑧0), in addition to the universal features of the number of quarks scaling for the elliptic flow parameter of the strongly interacting particles (hadrons), have concluded that the development of partonic collectivity during the QGP phase and before hadronization. Furthermore, the hydrodynamic models; assuming thermalization, have perfectly described the 𝑣2 data at low transverse momentum incorporating an equation of state for the QGP. Nevertheless, the unexpected measured non-zero finite values of 𝑣2 for hadrons at high transverse momentum, as well as the similar suppressions for the away side yields - where the away side is the opposite direction from where the collision occurred, and yield means the number of particles produced from the collision - of direct photons and neutral pions, present a challenge. Existing models, such as jet-quenching models have encountered difficulties in accurately describing such data. Furthermore, the surprising similarity in the measured 𝑣2 values between heavy flavor and light quarks raises questions about the thermalization of heavy quarks within the produced medium, a phenomenon that remains inadequately understood. These intriguing puzzles have prompted a critical examination of potential non-flow contributions to the measurements, as their presence could significantly impact the imposed constraints on medium transport parameters, e.g., viscosity and entropy. After all, the reaction plane angle is not directly measurable quantity in the experiment, and it depends on commonly used techniques; and there might be biases due to the method itself. The major non-flow contributions might arise from the jet fragmentation and its underlying mechanisms.PYTHIA simulation is an ideal environment to unfold the contributions from the jet fragmentation, as it contains no final state interactions. Accordingly, the aim of the presented work is to further validate the experimental results, using the same techniques as in the experimental work in determining the reaction plane angle and measuring the elliptic flow parameter 𝑣2(𝐸𝑃), using PYTHIA. PYTHIA was used to generate the data and simulating the high energy collisions at center-of-mass energies of √𝑆𝑁𝑁=200 GeV at RHIC and √𝑆𝑁𝑁=13 TeV at the LHC.